ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN PERSAMAAN KUADRAT PADA MATA KULIAH ALJABAR ELEMENTER - Firda Alfiana Patricia (Program Studi Pendidikan Matematika, 2019)
This study aims to describe student errors in solving quadratic equations in elementary algebra courses. Mistakes can teach students and lecturers to reflect. This research was conducted on students of 2018-B Mathematics Education program IKIP Budi Utomo Malang. Errors found include mistakes in facts, namely errors in understanding what is known in the problem. The principle error is that the formula used is not in accordance with the questions asked.